In Leaders We Trust, or Should We? Supervisors’ Dark Triad Personality Traits and Ratings of Team Performance and Innovation - Fodor, Oana C.; Curşeu, Petru L.; Meslec, Nicoleta (Frontiers in Psychology, 2021)
Our study tests in a sample of 87 organizational groups (297 employees and 87 supervisors) the mediating role of leader-member exchange (LMX) and collective narcissism in the relationship between supervisors’ dark triad (SDT) personality traits and ratings of team outcomes made by supervisors and team members. We show that LMX mediates the association between SDT and team performance and innovation as rated by team members, while collective narcissism mediates the association between SDT and supervisory ratings of team innovation and team performance. Moreover, collective narcissism also mediates the association between SDT and team innovation as rated by team members. Results show that team-level performance appraisal is influenced by supervisory attributes and that the quality of relational exchanges and collective narcissism are plausible mechanisms explaining this association. The use of supervisory ratings of team outcomes in empirical research should also account for the supervisory attributes.